Persuasive Communication of the BPJS Employment Program in the Palembang Branch for Traders at the Padang Selasa Market - Yolanda Tri Salsa*; Isnawijayani Isnawijayani (Universitas Syiah Kuala, 2023)
Persuasive communication will be effective if it can influence someone's attitude. Palembang Branch of BPJS Ketenagakerjaan is trying to persuade traders at Padang Selasa Market through socialization that has been carried out to educate and make traders aware of being able to take part in the labor social security program. This research aims to determine the persuasive communication of the Palembang branch of the BPJS Ketenagakerjan program for traders at the Padang Selasa Market. The method used in this research is a qualitative descriptive method. Using data collection techniques such as observation, interviews, and documentation. This research uses AIDDA theory to measure the effectiveness of persuasive communication used by the BPJS Ketenagakerjaan team when socializing with traders at the Padang Selasa Market. The results of this research are that the persuasive communication applied in socialization to Padang Selasa Market traders is quite effective seen from the persuasive communication techniques used and measured using AIDDA theory